18th AIAA/CEAS Aeroacoustics Conference (33rd AIAA Aeroacoustics Conference) 2012
DOI: 10.2514/6.2012-2124
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of trailing-edge serrations on open-rotor tonal noise

Abstract: Tonal noise of contra-rotating open rotors can be divided into self and interaction noise. The latter can be subdivided into potential field interaction noise, noise due to the interaction of the front-rotor wakes with the aft-rotor blades and tip vortex interaction noise. The excited tonal sound field is closely related to the properties of the impinging wakes provided that the tip vortex interaction is not the dominant source of interaction noise. Designing the trailing edge of the front-rotor blades with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Tonal interaction noise of the reference and the serrated configuration noise cancellation gets stronger. The analytically calculated spectra and the trend of increasing PWL reduction with higher frequencies agree with the results that Weckmüller et al [12] found with unsteady RANS and FW-H.…”
Section: Tonal Noisesupporting
confidence: 87%
See 2 more Smart Citations
“…Tonal interaction noise of the reference and the serrated configuration noise cancellation gets stronger. The analytically calculated spectra and the trend of increasing PWL reduction with higher frequencies agree with the results that Weckmüller et al [12] found with unsteady RANS and FW-H.…”
Section: Tonal Noisesupporting
confidence: 87%
“…Figure 5 shows a contour plot of the optimization area. In the optimization the engine orders up to 49 were considered for the tonal noise calculation for better comparability with the study done by Weckmüller et al [12]. In the optimization results a trend for the number and depth of the serrations can be identified.…”
Section: Results Of the Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The third objective related to the accurate prediction of tonal noise is achieved by coupling URANS solutions of the CFD solver TRACE to a far-field pressure extrapolation tool C3D_FWH (27,28,29) . A special formulation of the Ffowcs Williams and Hawkings method was developed for permeable surface in which the surface integration is replaced by a line integration thanks to an azimuthal decomposition of the flow-field solution (30) .…”
Section: Acousticsmentioning
confidence: 99%
“…In order to decrease the computation time and increase the accuracy, the phase-shift method was applied. The application of URANS to CROR is discussed by Schnell et al (10,20) and Weckmüller and Guérin (27,28) . The mesh strategy developed for CROR is presented in Fig.…”
Section: Numerical Approachmentioning
confidence: 99%